SISTEM INFORMASI DISTRIBUSI PUPUK BERSUBSIDI PADA KECAMATAN GERUNG LOMBOK BARAT - Ni Ketut Sriwinarti; Andres Faesal (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2015)
The accuracy of type, number, price, place, time and quality are the expectations that every farmer expects in the process of distributing and procurementing subsidized fertilizer. But the various alternatives which have already given or designed were not be able to solve the scarcity of fertilizer and it was happening very frequent in our environment. The usage of control card (farmer card) has been designed by goverment in 2007-2008 but it was not well distributed to all regions in East Nusa Tenggara. Whereas the usage of this card can be a good solution that can help in controling (managing) the fertilizer distribution so the fertilizer can be given to the appropriate farmers. The implementing of farmer card along with the making of information system of fertilzer distribution in Gerung is designed to solve the inaccuracies of subsidized feltilizer distribution. Every farmer registered in famer groups and RDKK (which is used by retailers to get the fertilizer) will get the identity card. By using the identity card farmers can come and show the identity card to retailers and then the retailers will see the identity and check the amount of fertilizer that each farmer has. By this system retails can distribute the fertilizer accurately in the term of target, quantity and price. Besides, this system also can help in observing the redeem that retailer did and the numbers of fertilizer sold.